2021
DOI: 10.3389/fphar.2021.713855
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices on the Use of Botanical Medicines in a Rural Caribbean Territory

Abstract: The worldwide use of medicinal plant products has been steadily increasing over the past few decades, whereas the traditional knowledge and practices of these botanical medicines appears to be diminishing. Considering the need to conserve and document these traditions, the objective of this study was to understand the knowledge, attitudes, and practices of people who are familiar with botanical medicines, as well as any factors that may influence the perceptions and behaviours associated with the use of medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This has led to a decline in the indigenous knowledge of medicinal plants. Similar results have been reported globally [49,50]. In contrast, Lulekal, Asfaw [48] reported that there was a signi cant difference in the understanding of medicinal plants between individuals with different levels of education, whether they were literate or illiterate.…”
Section: Threats To Ethnomedicnal Plants and Conservation Effortssupporting
confidence: 81%
“…This has led to a decline in the indigenous knowledge of medicinal plants. Similar results have been reported globally [49,50]. In contrast, Lulekal, Asfaw [48] reported that there was a signi cant difference in the understanding of medicinal plants between individuals with different levels of education, whether they were literate or illiterate.…”
Section: Threats To Ethnomedicnal Plants and Conservation Effortssupporting
confidence: 81%
“…Also, generational knowledge has been passed on to subsequent generations by shamans, curanderos, traditional healers, and herbalists . The older and more rural population is tied closer to these traditional practices and use herbal remedies more often for various ailments and diseases than their younger counterparts. , The older population in Barbados has one or more chronic conditions and may use different medicines concomitantly . Logically, the risk for drug–herb interactions is higher in this specific group of persons.…”
Section: Introductionmentioning
confidence: 99%